Caladium Cultivars Developed at the University of Florida/IFAS - Zhanao Deng; Brent K. Harbaugh (EDIS, 2005)
The University of Florida's Institute of Food and Agricultural Sciences (UF/IFAS) initiated a caladium breeding program in 1976 at the Gulf Coast Research and Education Center in Bradenton, Florida. So far, this has been the only major organized caladium breeding program in the world. The program's main objectives were to develop new cultivars that: 1) can produce many bright colorful leaves and a high yield of good quality tubers; and 2) have short, sturdy petioles and multi-eyed tubers that can result in increased early leaf production and improved leaf display. Additional goals of this program included the following: 1) to improve the aesthetic values and performance of caladium plants in containers and landscapes; 2) to eliminate the costly labor associated with tuber de-eyeing; and 3) to improve tuber and plant productivity and profitability. This document is ENH 965, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 25, 2003. Reviewed December 9, 2004.